responses to the COVID-19 pandemic in Nepal - Srivastava, Nandita; Nepal, Binisha; Gauchan, Biswash; Kennedy, Adam (International Food Policy Research Institute, 2021)
As soon as COVID-19 cases were reported in Nepal in early 2020, the Government of Nepal took several measures to minimize the spread of the virus and provide support to vulnerable groups. In addition to imposing a lockdown, the government took steps to bolster the health, financial and monetary, and business sectors. Despite these measures, capacity constraints in the health sector, political instability, and the return of a large pool of migrant workers to Nepal all contributed to increased spread of the disease and heightened vulnerability among the food insecure and those whose livelihoods were harmed by the lockdowns. This brief draws on the COVID-19 Response (CPR) Portal (IFPRI 2020) to summarize the policies put in place by the Government of Nepal to combat the virus, as well as some of the challenges with implementation.